Fluorine intercalated porous carbon nitride for simultaneous removal of pollutants in wastewater by oxidation-reduction method, and preparation method and application thereof

CN122912891APending Publication Date: 2026-10-16BEIJING UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510428865.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-07
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

但是,寻找合适的小分子掺杂源和共热条件是一道难题,如果选择不合适则会导致合成产物与预期不符,得到的g-C3N4结晶度较低、体相内导电性差、孔隙度较小且光吸收性能差,导致光催化活性较差

Benefits of technology

[0016] 1. This invention involves reacting melamine and ammonium fluoride in an open environment via oil bath heating to obtain a modified precursor. The modified precursor is then placed in a sealed crucible and subjected to a one-step high-temperature calcination in a closed environment. Subsequently, the resulting intermediate is placed in an open container for a second high-temperature calcination to obtain the modified F-CN photocatalyst. This is an effective and green method. Melamine itself is commonly used as a precursor for sintered graphite phase g-C3N4, while ammonium fluoride consists of strongly electronegative fluorine atoms and a unique ammonium group (NH4+). + The cationic composition is beneficial for modifying the graphitic phase g-C3N4. Compared with the unmodified form, its catalytic efficiency for ibuprofen (IBP, a typical example of nonsteroidal anti-inflammatory drugs) and U(VI) increased by 3.3 and 12.7 times, respectively, indicating that the modified F-CN material has excellent photocatalytic redox performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005347538930000011
    Figure HDA0005347538930000011
  • Figure HDA0005347538930000012
    Figure HDA0005347538930000012
  • Figure HDA0005347538930000021
    Figure HDA0005347538930000021
Patent Text Reader

Abstract

The application discloses a fluorine intercalation porous carbon nitride for synchronously purifying wastewater by an oxidation-reduction method and a preparation method and application thereof, and belongs to the field of catalysis. The preparation process of the catalyst is as follows: melamine and a fluorine salt mixture are placed in an open environment, ultrasonic dispersion, oil bath and high-temperature drying are carried out to obtain a precursor, the modified precursor is placed in a crucible and sealed, one-step high-temperature calcination is carried out, cooling to room temperature is carried out, then the obtained intermediate is placed in an open container to carry out secondary high-temperature calcination to obtain the target F-CN photocatalyst. Compared with before modification, the photocatalytic activity of the non-steroidal anti-inflammatory drug molecule oxidative degradation and the radioactive metal element uranyl reduction fixation is obviously improved, the removal rates of ibuprofen and U(VI) are up to about 100% and 89% respectively, the fluorine atoms are introduced into the interlayer of the modified graphite phase carbon nitride, the interlayer connection is enhanced, the interlayer electron transmission distance is reduced, the band gap is reduced, a strong photocurrent signal is generated, and the photo-generated carrier recombination is obviously inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of functional materials technology, specifically to a fluorine-intercalated porous carbon nitride, its preparation method, and its applications. Background Technology

[0002] Graphite-phase g-C3N4 (g-C3N4), as a common n-type semiconductor, possesses advantages such as good visible light response, strong physicochemical stability, resistance to photocorrosion, and low cost and ease of preparation. It has been extensively studied in fields such as photocatalytic hydrogen peroxide production, photocatalytic water splitting for hydrogen production, and photocatalytic reduction of heavy metal ions. g-C3N4 prepared by high-temperature calcination of nitrogen-rich precursors (such as dicyandiamide, thiourea, melamine, and urea) is commonly used in the purification of various wastewaters. However, g-C3N4 prepared by the common one-step sintering method suffers from drawbacks such as large particle size, high stacking degree, small porosity and specific surface area, the presence of uncondensed organic impurities on the surface, low visible light utilization, and poor conductivity. These drawbacks include low surface active sites, easy recombination of bulk photogenerated carriers, slow interfacial reaction rates, and low redox capacity, thus reducing photocatalytic activity. Therefore, there is an urgent need to develop new strategies to modify g-C3N4 to enhance its photocatalytic redox performance.

[0003] Raw materials, modification methods, and calcination processes have a decisive impact on the synthesized g-C3N4 catalyst. First, the C, N, and H elements in nitrogen-rich precursors mainly participate in the formation of the g-C3N4 framework. Differences in the molecular structure, elemental composition, and physicochemical properties of different precursors directly affect the microstructure and surface porosity of g-C3N4. Second, doping modification, by introducing other elements, can strengthen the in-plane triazine units and interlayer bonds, improving the polymerizability, crystallinity, and conductivity of the finished g-C3N4. Furthermore, changing the high-temperature calcination process and controlling the atmosphere of the thermopolymerization reaction can lead to the synthesis of different types of g-C3N4 through different condensation reactions of the precursor molecules and dopant sources. Combined with the differences in the elemental content in the precursor and dopant sources, this results in g-C3N4 having different surface active sites and interlayer bonding modes, thus affecting the atomic arrangement and layered stacking form within the g-C3N4 framework. The aforementioned factors directly determine the microstructure, phase crystal form, and electronic energy level structure of the g-C3N4 finished catalyst, including the precursor material, doping source, and calcination process. Specifically, this manifests as the photocatalytic oxidative degradation of nonsteroidal anti-inflammatory drug molecules in wastewater and the photocatalytic reduction and enrichment of the radioactive nuclide uranyl.

[0004] Generally, precursor doping modification methods mainly use other small molecule compounds as dopant sources, modifying them through solvothermal co-treatment. However, finding suitable small molecule dopant sources and co-heating conditions is a challenge. Inappropriate selection can lead to unintended synthesized products, resulting in g-C3N4 with low crystallinity, poor bulk conductivity, small porosity, and poor light absorption, leading to poor photocatalytic activity. Furthermore, selecting appropriate calcination processes, including temperature and ambient atmosphere, is an effective way to optimize the active sites on the catalyst surface. Typically, a secondary calcination process under air or oxygen conditions can further remove impurities and unreacted organic molecule residues from the surface of the g-C3N4 catalyst at high temperatures, improving the exposure and utilization rate of active sites. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to address the shortcomings of the prior art by providing a fluorine-intercalated porous g-C3N4 photocatalyst (F-CN) that can be used simultaneously for the oxidative degradation treatment of wastewater containing non-steroidal anti-inflammatory drug molecules or the reduction and fixation of uranyl wastewater, and its preparation method. The present invention uses melamine as a precursor and ammonium fluoride as a dopant source. The modified precursor is obtained by ultrasonic dispersion, oil bath and high temperature drying in an open environment. After being placed in a crucible and sealed, it is subjected to a one-step high temperature calcination. Then the obtained intermediate is placed in an open container for a second high temperature calcination to obtain the target F-CN photocatalyst. The photocatalytic oxidation and reduction tests using the optimized target F-CN as a catalyst in this invention showed that, compared with the unmodified version, the photocatalytic activity for the oxidative degradation of nonsteroidal anti-inflammatory drug molecules and the reduction and fixation of radioactive metal nuclide uranyl (U(VI)) was significantly improved. The catalytic efficiency for ibuprofen (a typical example of a pollutant) and U(VI) was increased by 3.3 and 12.7 times, respectively. The graphite phase g-C3N4 modified by the method of this invention introduces a rich porous structure, and the aromatic heterocyclic plane is modified by fluorine atom intercalation, which enhances the interlayer bonding effect, reduces the interlayer electron transport distance, and has a stronger photocurrent response and lower internal resistance. This effectively accelerates the transport and separation of photogenerated carriers, thereby suppressing the separation of photogenerated carriers and improving the utilization rate of light quanta.

[0006] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing an F-CN photocatalyst for simultaneous wastewater oxidation or reduction treatment is characterized in that a mixture of melamine and ammonium fluoride is prepared into a solution and placed in an open environment for ultrasonic dispersion, oil bath, and high-temperature drying to obtain a modified precursor. The modified precursor is placed in a crucible, sealed, and then subjected to a one-step high-temperature calcination. After cooling to room temperature, the obtained intermediate is placed in an open container for a second high-temperature calcination to obtain the target F-CN photocatalyst.

[0008] The melamine and ammonium fluoride were mixed with water as a dispersant to prepare a solution.

[0009] The molar ratio of melamine to ammonium fluoride is 1:0.01 to 1.

[0010] The molar ratio of melamine to ammonium fluoride is 1:0.1 to 1.

[0011] The molar ratio of melamine to ammonium fluoride is 1:0.2.

[0012] In the oil bath heating reaction of melamine and ammonium fluoride, the oil bath temperature control program is set to 40-90℃ and maintained for 2-12 hours;

[0013] In the two-step high-temperature calcination reaction of the modified precursor, the temperature control program for the first step reaction is set as follows: the temperature is increased to 450-600℃ within 100-500 min and held for 3-6 h; the temperature control program for the second step reaction is set as follows: the temperature is increased to 400-600℃ within 50-150 min and held for 1-3 h.

[0014] The fluorine-intercalated porous carbon nitride obtained in this invention can be used for photocatalytic oxidation degradation of nonsteroidal anti-inflammatory drugs and photocatalytic reduction fixation of U(VI) in aqueous solution.

[0015] Compared with the prior art, the present invention has the following advantages:

[0016] 1. This invention involves reacting melamine and ammonium fluoride in an open environment via oil bath heating to obtain a modified precursor. The modified precursor is then placed in a sealed crucible and subjected to a one-step high-temperature calcination in a closed environment. Subsequently, the resulting intermediate is placed in an open container for a second high-temperature calcination to obtain the modified F-CN photocatalyst. This is an effective and green method. Melamine itself is commonly used as a precursor for sintered graphite phase g-C3N4, while ammonium fluoride consists of strongly electronegative fluorine atoms and a unique ammonium group (NH4+). + The cationic composition is beneficial for modifying the graphitic phase g-C3N4. Compared with the unmodified form, its catalytic efficiency for ibuprofen (IBP, a typical example of nonsteroidal anti-inflammatory drugs) and U(VI) increased by 3.3 and 12.7 times, respectively, indicating that the modified F-CN material has excellent photocatalytic redox performance.

[0017] 2. The modified F-CN exhibits superior photocatalytic activity, mainly due to: ① its porous structure; ② enhanced interlayer bonding, reducing electron transport distance; ③ regulation of electronic energy level structure, reducing band gap; ④ enhanced visible light absorption performance and photocurrent response; ⑤ reduced internal resistance; ⑥ enhanced photocurrent response; and ⑦ suppression of photogenerated carrier recombination. Furthermore, melamine can be mixed with other small-molecule inorganic halide salts and reacted in an oil bath to obtain a new precursor, which can then be calcined at high temperature to further modify the original g-C3N4.

[0018] The preparation method of the present invention has the advantages of simple operation, mild reaction conditions, readily available raw materials, and good reproducibility. The resulting product has the advantages of simple process for oxidative degradation of non-steroidal anti-inflammatory drug molecules (using ibuprofen as a typical example of pollutant, preferably up to 100% degradation) or reduction and enrichment of U(VI) in water. It is not limited by atmosphere, has high removal efficiency, strong recyclability, environmental friendliness, and wide range of applications, and has broad application value. Attached Figure Description

[0019] Figure 1 The bar charts show the photocatalytic activity of the photocatalysts in Examples 1-4 and Comparative Example 1; where (a) represents the catalytic performance of oxidative degradation of ibuprofen and (b) represents the catalytic performance of reduction fixation of U(VI).

[0020] Figure 2 The bar charts show the photocatalytic activity of the photocatalysts in Examples 1 and 5-7. Figure 3 The bar charts show the photocatalytic activity of the photocatalysts in Examples 1 and 8-10. Figure 4 The bar charts show the photocatalytic activity of the photocatalysts in Examples 1 and 11-13. Figure 5 The bar charts show the photocatalyst activity of Example 1 and Comparative Example 2.

[0021] Figure 6 F prepared in Example 1 of this invention 0.2 Characterization images and simulated structural diagrams of the -CN photocatalyst; where (a) is a scanning electron microscope image, (b) is a transmission electron microscope image, and (c) is a simulated molecular structure diagram.

[0022] Figure 7 F of Example 1 0.2 XRD patterns of g-C3N4 prepared by conventional method in Example 3 and Comparative Example 1; where (a) shows that the XRD patterns are basically the same; (b) shows that the interlayer spacing of the product in Example 3 is smaller.

[0023] Figure 8 F of Example 1 0.2 FTIR spectra of -CN and comparative example 1g-C3N4.

[0024] Figure 9F of Example 1 0.2 The light absorption performance characterization images of -CN and comparative example 1g-C3N4; where (a) is the UV-Vis curve and (b) is the corresponding Tauc curve.

[0025] Figure 10 F of Example 1 0.2 -CN cycle photocatalytic degradation of ibuprofen and reduction of fixed U(VI) activity bar chart.

[0026] Figure 11 F of Example 1 0.2 -CN photocatalytic oxidation degradation of different nonsteroidal anti-inflammatory drugs activity bar chart. Detailed Implementation

[0027] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. The technical solutions of the present invention are not limited to the specific embodiments listed below, but also include any combination of the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0028] In this invention, unless specific techniques or conditions are specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field, or in accordance with the product instructions. Instruments and other equipment whose manufacturers are not specified are all conventional products that can be purchased through legitimate channels. All chemical raw materials used in this invention are readily available in the domestic chemical product market.

[0029] This invention discloses a fluorine-intercalated porous g-C3N4 photocatalyst (F-CN) for simultaneous oxidative degradation treatment of wastewater containing non-steroidal anti-inflammatory drugs or reduction fixation of wastewater containing uranyl esters, and its preparation method, comprising the following steps: in an open environment, melamine and ammonium fluoride are ultrasonically dispersed, subjected to oil bath, and high-temperature drying to obtain a modified precursor, which is placed in a crucible, sealed, and then subjected to a first-step high-temperature calcination. Then, the obtained intermediate is placed in an open container for a second high-temperature calcination. By changing the airtightness of the crucible, the calcination environment atmosphere is controlled, and finally, the optimized target F-CN photocatalyst is obtained.

[0030] A fluorine-intercalated porous g-C3N4 photocatalyst (F-CN) for simultaneous oxidative degradation treatment of wastewater containing non-steroidal anti-inflammatory drugs or reduction fixation of wastewater containing uranyl esters, and its preparation method are disclosed. The present invention uses melamine as a precursor and ammonium fluoride as a dopant source. The modified precursor is obtained by ultrasonic dispersion, oil bath, and high-temperature drying in an open environment. After being placed in a crucible and sealed, it is subjected to a one-step high-temperature calcination. Then, the obtained intermediate is placed in an open container to fully contact with air for a second high-temperature calcination, and finally fluorine-intercalated porous g-C3N4 is obtained.

[0031] Specifically, the procedure is as follows: the molar ratio of melamine to ammonium fluoride is 1:0.01 to 1, that is, the molar amount of melamine is a fixed value of 0.04 mol, the molar amount of ammonium fluoride varies between 0.0004 and 0.04 mol, and the dispersant is water.

[0032] The oil bath heating reaction described in this invention includes: heating to 40-90℃ and holding for 2-12 hours. In the two-step high-temperature calcination reaction of the modified precursor, the environmental atmosphere of the high-temperature calcination is controlled by adjusting the airtightness of the supporting container. The reaction conditions and temperature control program for the first step are set as follows: the modified precursor is placed in a crucible and sealed, and then the temperature is raised to 450-600℃ within 100-500 minutes and held for 3-6 hours. The reaction conditions and temperature control program for the second step are set as follows: the intermediate obtained in the first step is placed in an open container, and then the temperature is raised to 400-600℃ within 50-150 minutes and held for 1-3 hours. Specific reaction parameters can be adjusted, such as the molar amount of ammonium fluoride being 0.003 mmol, 0.005 mmol, 0.008 mmol, or 0.014 mmol, the oil bath temperature being 40℃, 60℃, 80℃, or 90℃, the first sintering temperature being 450℃, 500℃, 550℃, or 600℃, and the second sintering temperature being 400℃, 450℃, 500℃, or 600℃. Graphite-phase carbon nitride prepared by treating melamine and ammonium fluoride in an oil bath and then calcining and activating them twice at high temperatures under different environmental atmospheres is modified, giving the modified graphite-phase carbon nitride good photocatalytic activity.

[0033] The following description, in conjunction with specific embodiments, illustrates the content of the present invention. However, the following description is not intended to limit the scope of the present invention.

[0034] Example 1

[0035] This embodiment provides a fluorine-intercalated porous g-C3N4 photocatalyst for simultaneous oxidative degradation treatment of wastewater containing nonsteroidal anti-inflammatory drugs or reduction fixation of wastewater containing uranyl esters, wherein the molar ratio of melamine to ammonium fluoride is 1:0.2.

[0036] This embodiment provides a method for preparing a graphite-phase carbon nitride photocatalyst for wastewater treatment, including:

[0037] Step 1: Take 0.04 mol of melamine and about 0.008 mol of ammonium fluoride, add water as a dispersant under ultrasonic conditions, and sonicate for 20 minutes to ensure that the precursor and dopant source are completely and evenly dispersed.

[0038] Step 2: Place the dispersion system described in Step 1 into an open glass reactor;

[0039] Step 3: Place the glass reactor described in Step 2 into an oil bath, then heat it to 80°C while stirring magnetically for 6 hours.

[0040] Step 4: Stir the water dispersant in the system after the reaction in Step 3 until it is completely dry to obtain melamine pretreated with dopant source;

[0041] Step 5: Grind all of the precursors obtained in Step 4 and place them in a crucible;

[0042] Step 6: After sealing the crucible (50ml volume) described in Step 5, place it in a muffle furnace, and then heat it to 550℃ in 250min and maintain it for 4h; In this embodiment, programmed heating is used to raise the temperature from room temperature to 550℃ in 250min.

[0043] Step 7: Grind the sample after the reaction in Step 6, weigh 2g and place it in an open container. Put it in a muffle furnace, and then heat it to 500℃ in 100min and keep it for 2h.

[0044] Step 8: Grind the sample after the reaction in Step 7 to obtain the modified F. 0.2 -CN photocatalyst; where 0.2 represents the molar ratio of ammonium fluoride to melamine added.

[0045] Example 2

[0046] This embodiment is the same as Example 1, except that the molar ratio of ammonium fluoride to melamine added in step one is 0.07, resulting in the modified graphitic carbon nitride photocatalyst F. 0.07 -CN; where 0.07 represents the molar ratio of ammonium fluoride to melamine added.

[0047] Example 3

[0048] This embodiment is the same as Example 1, except that the molar ratio of ammonium fluoride to melamine added in step one is 0.14, resulting in the modified graphitic carbon nitride photocatalyst F. 0.14 -CN; where 0.14 represents the molar ratio of ammonium fluoride to melamine added.

[0049] Example 4

[0050] This embodiment is the same as Example 1, except that the molar ratio of ammonium fluoride to melamine added in step one is 0.34, resulting in the modified graphitic carbon nitride photocatalyst F. 0.34 -CN; where 0.34 represents the molar ratio of ammonium fluoride to melamine added.

[0051] Example 5

[0052] This embodiment is the same as that in Embodiment 1, except that the oil bath reaction temperature in step three is 40°C.

[0053] Example 6

[0054] This embodiment is the same as Embodiment 1, except that the oil bath reaction temperature in step three is 60°C.

[0055] Example 7

[0056] This embodiment is the same as Embodiment 1, except that the oil bath reaction temperature in step three is 90°C.

[0057] Example 8

[0058] This embodiment is the same as Embodiment 1, except that the sintering temperature in step six is ​​450°C.

[0059] Example 9

[0060] This embodiment is the same as Embodiment 1, except that the sintering temperature in step six is ​​500°C.

[0061] Example 10

[0062] This embodiment is the same as Embodiment 1, except that the sintering temperature in step six is ​​600°C.

[0063] Example 11

[0064] This embodiment is the same as Embodiment 1, except that the sintering temperature in step seven is 400°C.

[0065] Example 12

[0066] This embodiment is the same as Embodiment 1, except that the sintering temperature in step seven is 450°C.

[0067] Example 13

[0068] This embodiment is the same as Embodiment 1, except that the sintering temperature in step seven is 600°C.

[0069] Comparative Example 1

[0070] Step 1: Weigh 10g of melamine and place it in a covered crucible;

[0071] Step 2: Place the crucible described in Step 1 into a muffle furnace, and then heat it to 550°C in 250 minutes and maintain the temperature for 4 hours. In this embodiment, a programmed temperature rise is used to raise the temperature from room temperature to 550°C in 250 minutes.

[0072] Step 3: Grind the sample after the reaction in Step 2 to obtain the graphite phase carbon nitride photocatalyst g-C3N4.

[0073] Comparative Example 2

[0074] Step 1: Take 0.04 mol of melamine and about 0.008 mol of ammonium fluoride, add water as a dispersant under ultrasonic conditions, and sonicate for 20 minutes to ensure that the precursor and dopant source are completely and evenly dispersed.

[0075] Step 2: Place the dispersion system described in Step 1 into an open glass reactor;

[0076] Step 3: Place the glass reactor described in Step 2 into an oil bath, then heat it to 80°C while stirring magnetically for 6 hours.

[0077] Step 4: Stir the water dispersant in the system after the reaction in Step 3 until it is completely dry to obtain melamine pretreated with dopant source;

[0078] Step 5: Grind all of the precursors obtained in Step 4 and place them in a crucible;

[0079] Step 6: After sealing the crucible described in Step 5, place it in a muffle furnace, and then heat it to 550°C in 250 minutes and maintain the temperature for 4 hours. In this embodiment, a programmed temperature rise is used to raise the temperature from room temperature to 550°C in 250 minutes.

[0080] Step 7: Grind the sample after the reaction in Step 6, weigh 2g and place it in a sealed container. Put the container into a muffle furnace, and then heat it to 500℃ for 100min and keep it for 2h.

[0081] Step 8: Grind the sample after the reaction in Step 7 to obtain the modified graphitic carbon nitride photocatalyst F. 0.2 -CN-s.

[0082] Performance evaluation:

[0083] Figure 1 The bar charts show the photocatalytic activity of the photocatalysts in Examples 1-4 and Comparative Example 1; where (a) represents the catalytic performance of oxidative degradation of ibuprofen and (b) represents the catalytic performance of reduction fixation of U(VI).

[0084] The test method for the photocatalytic oxidation degradation performance of ibuprofen includes: dispersing 25 mg of photocatalyst in 50 mL of 10 mg / L ibuprofen solution, adding potassium persulfate (50 mg) as an auxiliary oxidant, maintaining the initial solution pH (~7.0), reacting for 60 min under visible light (λ>420 nm) irradiation, and quantifying the amount of oxidation degradation by detecting the change in ibuprofen concentration in the photocatalytic system.

[0085] The test method for the photocatalytic reduction and fixation performance of U(VI) includes: dispersing 20 mg of photocatalyst in 40 mL of 50 mg / L U(VI) solution, adding methanol (5 vol%) as a hole sacrificial agent, reacting under visible light (λ>420 nm) for 120 min, and quantifying the reduction and fixation amount by detecting the change in U(VI) concentration in the photocatalytic system using a colorimetric method.

[0086] according to Figure 1 It can be seen that, compared with g-C3N4 prepared by the traditional method (i.e., Comparative Example 1), the F-CN photocatalyst obtained by the modification method used in this invention has a significantly improved average photocatalytic efficiency. After 60 min of photoreaction, the photocatalytic degradation efficiency of ibuprofen by the F-CN catalyst reached 61%–99%, and after 120 min of photoreaction, the photocatalytic reduction and fixation efficiency of U(VI) by the F-CN catalyst reached 21%–89%, among which sample F 0.2 -CN (Example 1) exhibits the best catalytic performance.

[0087] Figure 2 The bar charts show the photocatalytic activity of the photocatalysts in Examples 1 and 5-7.

[0088] The test method for the photocatalytic oxidation degradation performance of ibuprofen includes: dispersing 25 mg of photocatalyst in 50 mL of 10 mg / L ibuprofen solution, adding potassium persulfate (50 mg) as an auxiliary oxidant, maintaining the initial solution pH (~7.0), reacting under visible light (λ>420 nm) for 60 min, and then quantifying the amount of oxidation degradation by detecting the change in ibuprofen concentration in the photocatalytic system.

[0089] The test method for the photocatalytic reduction and fixation performance of U(VI) includes: dispersing 20 mg of photocatalyst in 40 mL of 50 mg / L U(VI) solution, adding methanol (5 vol%) as a hole sacrificial agent, reacting under visible light (λ>420 nm) for 120 min, and then quantifying the reduction and fixation amount by detecting the change in U(VI) concentration in the photocatalytic system using a colorimetric method.

[0090] Depend on Figure 2 It can be seen that when the oil bath temperature is 80℃, the present invention F 0.2-CN photocatalyst exhibits the best removal effect, with a photodegradation efficiency of up to 99% for ibuprofen after 60 min of photoreaction, and a photoreduction and fixation efficiency of up to 89% for U(VI) after 120 min of photoreaction.

[0091] Figure 3 The bar chart shows the photocatalytic activity of the photocatalysts in Examples 1 and 8-10.

[0092] The test method for the photocatalytic oxidation degradation performance of ibuprofen includes: dispersing 25 mg of photocatalyst in 50 mL of 10 mg / L ibuprofen solution, adding potassium persulfate (50 mg) as an auxiliary oxidant, maintaining the initial solution pH (~7.0), reacting under visible light (λ>420 nm) for 60 min, and then quantifying the amount of oxidation degradation by detecting the change in ibuprofen concentration in the photocatalytic system.

[0093] The test method for the photocatalytic reduction and fixation performance of U(VI) includes: dispersing 20 mg of photocatalyst in 40 mL of 50 mg / L U(VI) solution, adding methanol (5 vol%) as a hole sacrificial agent, reacting under visible light (λ>420 nm) for 120 min, and then quantifying the reduction and fixation amount by detecting the change in U(VI) concentration in the photocatalytic system using a colorimetric method.

[0094] Depend on Figure 3 It can be seen that when the first sintering temperature is 550℃, the F of this invention... 0.2 -CN photocatalyst exhibited the best removal effect, with up to 99% photodegradation of ibuprofen after 60 min of photoreaction, and 89% photoreduction efficiency of U(VI) after 120 min of photoreaction.

[0095] Figure 4 The bar charts show the photocatalytic activity of the photocatalysts in Examples 1 and 11-13.

[0096] The test method for the photocatalytic oxidation degradation performance of ibuprofen includes: dispersing 25 mg of photocatalyst in 50 mL of 10 mg / L ibuprofen solution, adding potassium persulfate (50 mg) as an auxiliary oxidant, maintaining the initial solution pH (~7.0), reacting for 60 min under visible light (λ>420 nm) irradiation, and quantifying the amount of oxidation degradation by detecting the change in ibuprofen concentration in the photocatalytic system.

[0097] The test method for the photocatalytic reduction and fixation performance of U(VI) includes: dispersing 20 mg of photocatalyst in 40 mL of 50 mg / L U(VI) solution, adding methanol (5 vol%) as a hole sacrificial agent, reacting under visible light (λ>420 nm) for 120 min, and quantifying the reduction and fixation amount by detecting the change in U(VI) concentration in the photocatalytic system using a colorimetric method.

[0098] Depend on Figure 4 It can be seen that when the sintering temperature in the second step is 500℃, the F of this invention... 0.2 -CN photocatalyst exhibited the best removal effect, achieving 99% photodegradation of ibuprofen after 60 min of photoreaction, and 89% photoreduction efficiency of U(VI) after 120 min of photoreaction.

[0099] Figure 5 The bar charts show the photocatalyst activity of Example 1 and Comparative Example 2.

[0100] The test method for the photocatalytic oxidation degradation performance of ibuprofen includes: dispersing 25 mg of photocatalyst in 50 mL of 10 mg / L ibuprofen solution, adding potassium persulfate (50 mg) as an auxiliary oxidant, maintaining the initial solution pH (~7.0), reacting for 60 min under visible light (λ>420 nm) irradiation, and quantifying the amount of oxidation degradation by detecting the change in ibuprofen concentration in the photocatalytic system.

[0101] The test method for the photocatalytic reduction and fixation performance of U(VI) includes: dispersing 20 mg of photocatalyst in 40 mL of 50 mg / L U(VI) solution, adding methanol (5 vol%) as a hole sacrificial agent, reacting under visible light (λ>420 nm) for 120 min, and quantifying the reduction and fixation amount by detecting the change in U(VI) concentration in the photocatalytic system using a colorimetric method.

[0102] It can be seen that, compared to F prepared by secondary calcination after container sealing, 0.2 -CN-s (i.e., Comparative Example 2), the F obtained by secondary high-temperature calcination in an open container used in this invention 0.2 -CN photocatalysts significantly improve the efficiency of photocatalytic oxidation degradation of ibuprofen and reduction fixation of U(VI), which are approximately Fi and Fi, respectively. 0.2 The photocatalytic efficiency of -CN-s is ~2.2 and 2.3 times that of CN-s, indicating that the open container may provide sufficient oxygen, which leads to the removal of surface organic impurities during the secondary high-temperature calcination process, exposing more active sites.

[0103] Figure 6 For F 0.2 Characterization images and simulated structural diagrams of -CN (Example 1). From the scanning electron microscope (SEM) images, transmission electron microscope (TEM) images, and simulated molecular structure diagrams, it can be seen that F...0.2 -CN exhibits a porous structure and a heptaazine ring carbon-nitrogen heterocyclic planar structure. Furthermore, F atoms intercalate into the g-C3N4 interlayer by forming CF bonds with C atoms, indicating that oil bath reaction treatment and two-step high-temperature calcination induce the formation of CF bonds and enhance interlayer interactions.

[0104] Figure 7 For F 0.2 XRD patterns of -CN (Example 1) and g-C3N4 (Comparative Example 1). From (a), it can be seen that F... 0.2 The XRD spectra of -CN and g-C3N4 are basically consistent, indicating that the crystal structure of the graphitic carbon nitride prepared by two-step high-temperature calcination after oil bath heating reaction treatment of the precursor has not changed. From (b), it can be seen that F 0.2 The XRD peaks of -CN are broadened and weakened, and the peaks shift to higher angles, indicating that the interlayer spacing is reduced and the interlayer interaction is strengthened.

[0105] Figure 8 For F 0.2 FTIR spectra of -CN (Example 1) and g-C3N4 (Comparative Example 1). As shown in the figure, F... 0.2 The FTIR spectra of -CN and g-C3N4 are basically consistent, indicating that the molecular structure of the graphitic carbon nitride prepared by the two-step calcination after the oil bath heating reaction of the precursor has not changed.

[0106] Figure 9 For F 0.2 The light absorption performance characterization analysis of -CN (Example 1) and g-C3N4 (Comparative Example 1) includes (a) UV-Vis curves and (b) the corresponding Tauc curves. As shown in the figures, with the introduction of interlayer doping of F atoms, the light absorption capacity of the modified samples is enhanced, the electronic energy level structure changes, the band gap decreases, and the background absorption of the UV-Vis curve becomes stronger, indicating the introduction of more defects.

[0107] Figure 10 For F 0.2 -CN (Example 1) Activity bar chart of photocatalytic degradation of ibuprofen and reduction of fixed U(VI). As shown in the figure, after multiple cycles of the modified graphitic carbon nitride catalyst obtained by pretreatment of melamine and ammonium fluoride in an oil bath followed by two-step high-temperature calcination, the photocatalytic degradation efficiencies of ibuprofen and reduction of fixed U(VI) remained as high as 97% and 85%, respectively. This indicates that the modified catalyst possesses good chemical stability and strong reaction reproducibility, demonstrating its broad application value.

[0108] Figure 11 For F 0.2-CN (Example 1) Activity bar chart of photocatalytic oxidation degradation of different nonsteroidal anti-inflammatory drugs. As shown in the figure, the modified graphitic carbon nitride photocatalyst obtained by pretreatment of melamine and ammonium fluoride in an oil bath followed by two-step high-temperature calcination exhibits degradation and removal efficiencies of >90% for various nonsteroidal anti-inflammatory drug organic pollutants, including ibuprofen (IBP), acetaminophen (APAP), aspirin (ASA), diclofenac (DCF), naproxen (NPX), ketoprofen (KTP), and meloxicam (MLX). This indicates that the modified catalyst has universal applicability to the photo-Fenton catalytic degradation of pollutants containing nonsteroidal anti-inflammatory drugs and is suitable for large-scale industrial applications.

[0109] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is not intended to limit the present invention in any way. Any simple modifications, alterations, and equivalent structural changes made to the above embodiments based on the technical essence of the invention shall still fall within the protection scope of the present invention.

Claims

1. A method for preparing a fluorine-intercalated porous carbon nitride photocatalyst for simultaneous wastewater oxidation or reduction treatment, characterized in that, Includes the following steps: A mixture of melamine and ammonium fluoride was prepared into a solution and placed in an open environment for ultrasonic dispersion, oil bath, and high-temperature drying to obtain a modified precursor. The modified precursor was placed in a crucible, sealed, and then subjected to a one-step high-temperature calcination. After cooling to room temperature, the resulting intermediate was placed in an open container for a second high-temperature calcination to obtain the target F-CN photocatalyst.

2. The method for preparing a fluorine-intercalated porous carbon nitride photocatalyst for simultaneous wastewater oxidation or reduction treatment according to claim 1, characterized in that, The melamine and ammonium fluoride were mixed with water as a dispersant to prepare a solution.

3. The method for preparing a fluorine-intercalated porous carbon nitride photocatalyst for simultaneous wastewater oxidation or reduction treatment according to claim 1, characterized in that, The molar ratio of melamine to ammonium fluoride is 1:0.01 to 1.

4. A method for preparing a fluorine-intercalated porous carbon nitride photocatalyst for simultaneous wastewater oxidation or reduction treatment according to claim 1, characterized in that, The molar ratio of melamine to ammonium fluoride is 1:0.1 to 1.

5. A method for preparing a fluorine-intercalated porous carbon nitride photocatalyst for simultaneous wastewater oxidation or reduction treatment according to claim 1, characterized in that, The molar ratio of melamine to ammonium fluoride is 1:0.

2.

6. A method for preparing a fluorine-intercalated porous carbon nitride photocatalyst for simultaneous wastewater oxidation or reduction treatment according to claim 1, characterized in that, In the oil bath heating reaction of melamine and ammonium fluoride, the oil bath temperature control program is set to 40-90℃ and maintained for 2-12 hours.

7. A method for preparing a fluorine-intercalated porous carbon nitride photocatalyst for simultaneous wastewater oxidation or reduction treatment according to claim 1, characterized in that, In the two-step high-temperature calcination reaction of the modified precursor, the temperature control program for the first step reaction is set as follows: the temperature is increased to 450-600℃ within 100-500 min and held for 3-6 h; the temperature control program for the second step reaction is set as follows: the temperature is increased to 400-600℃ within 50-150 min and held for 1-3 h.

8. A fluorine-intercalated porous carbon nitride photocatalyst prepared according to any one of claims 1-7.

9. The application of the fluorine-intercalated porous carbon nitride photocatalyst prepared according to any one of claims 1-7, for photocatalytic oxidation degradation of nonsteroidal anti-inflammatory drugs and photocatalytic reduction fixation of U(VI) in aqueous solution.

10. The application according to claim 9, wherein the light is visible light (λ>420nm); the degradation and removal efficiency of nonsteroidal anti-inflammatory drugs including ibuprofen (IBP), acetaminophen (APAP), aspirin (ASA), diclofenac (DCF), naproxen (NPX), ketoprofen (KTP), and meloxicam (MLX) is as high as >90%; and the efficiency of reducing and fixing U(VI) reaches 97%.